Recurrence of substantiated maltreatment reports between low-income parents with disabilities and their propensity-score matched sample without disabilities - Cho, Minhae (Child maltreatment, 2023)
Using the Longitudinal Studies of Child Abuse and Neglect dataset, 127 low-income parents with disabilities and a propensity score matched sample of 254 parents without disabilities were compared for the rates of repeated substantiated child maltreatment allegations and potentially distinct risks for substantiated child maltreatment recurrence. The number of substantiated child maltreatment allegations was not significantly higher for low-income parents with disabilities (M = 1.17, SD = 1.83) than their matched sample (M = .93, SD = 1.44) (t = ?1.29, p = .197). Findings from the negative binomial regression indicated that parental disability was also not a significant predictor for repeated substantiated child maltreatment allegations among low-income parents after controlling other risk factors (Exp(B) = 1.16, p < .353). In both groups, black parents were more likely to have repeated substantiated maltreatments than white parents. For parents with disabilities, being an older parent, receiving SNAP benefits, having a daughter, and having a child in continued out-of-home care significantly increased the risk for repeated substantiations while having a GED or higher education degree and living with a larger number of family decreased the risk. For parents without disabilities, family instability was the only additional risk factor for repeated maltreatment substantiations.